Genetic population structure of the toxigenic dinoflagellate Alexandrium catenella in the Patagonian Fjords System, southern Chile - Paredes-Mella, Javier; Varela, Daniel (Revista de Biología Marina y Oceanografía, 2020)
Alexandrium catenella is the main species that form harmful algae blooms (HABs) in southern Chile. Since its first record in 1972 in the Magallanes region this species apparently has increased its range distribution from south to north. In this study, we investigate the influence of the range expansions distribution on the A. catenella populations genetic diversity and structure. This was achieved by isolating 33 clones from different localities along the Magallanes and Aysén region which were genetically characterized with Amplified Fragment Length Polymorphism (AFLPs) molecular markers. Results showed a latitudinal genetic diversity gradient from the south to north populations. Inter-populations genetic divergences were low but significant between both geographically close and distant populations. Results indicated that the genetic diversity differentiation could be generated by a founder effect, which is expected in populations that have expanded their distribution range. On the other hand, low levels of genetic divergences between distant populations seems point out that high gene flow occurs along coast of the Pacific Ocean, but also, seems hints the connectivity route between the Magallanes and Aysén populations i.e., the vegetative cells dispersion among populations, would occur through coastal Pacific coast and Boca del Guafo. Finally, the high values of multilocus linkage disequilibrium found between closer population of Aysén indicates that divergence could be influenced along with the reproductive dynamic of the vegetative cells.